DAMPAK PERBEDAAN LAJU AERASI SELAMA FERMENTASI TERHADAP KUALITAS BIOETANOL BERBAHAN MOLASE - Tri Rachmanto; I Made Adi Sayoga; Fardiaz Anugrah Saputra (Energy, Materials and Product Design, 2026)
Energy consumption is increasing along with the increase in population. At this time the use of energy can not be separated from everyday life. Energy needs still depend on fossil energy resources or petroleum. Bioethanol is a potential non-fossil fuel and can be used as an alternative fuel. Plants that can be used as bioethanol are starchy materials such as cassava, sweet potatoes, wheat and potatoes; sugary ingredients such as molasses (molasses). The purpose of this study was to determine the effect of variations in the rate of aeration during fermentation on the quality of bioethanol produced with molasses. Parameters of bioethanol quality observed were bioethanol content, volume of bioethanol, and calorific value. This study used variations in the rate of aeration during fermentation of 1 lpm, 1.5 lpm, and 2 lpm. Bioethanol is produced by fermenting molasses for 72 hours (3 days), then a distillation process is carried out to obtain bioethanol from molasses fermentation. The study produced the highest average bioethanol content and average bioethanol  volume  produced at an aeration rate of 2 lpm with an average bioethanol content of 86.67%. and an average bioethanol volume of 346.67 ml. The higher the alcohol content produced, the higher the calorific value. The highest calorific value was obtained from the 2 lpm variation with a sample content of 90% with a calorific value of 12456.60 Joules/g.